Label free non-invasive imaging of topically applied actives in reconstructed human epidermis by confocal Raman spectroscopy - Fleischli, Franziska D.; Mathes, Stephanie; Adlhart, Christian (Vibrational spectroscopy, 2013)
Raman spectroscopy has become a versatile tool for the in vivo characterization of skin. Here we describe use of Raman spectroscopy for high resolution optical cross sectioning to resolve skin constituents and administered drugs at the cellular level. Percutaneous penetration is typically studied using permeation cells with biopsies of animals or human skin. Although this technique provides valuable clinical data, little insight is gained in the microstructure of drug penetration (intercellular or transcellular) or in the mode of action of applied vehicles or penetration enhancers. Therefore, a Raman microspectroscopic method was combined with a confocal scanning setup to image the microstructure of commercially available skin models (SkinEthic®) and the spatial distribution of penetrated actives. The models’ microstructure was scanned without any special treatment or environment such as cutting, staining, freezing, or application of vacuum. The non-invasive Raman images reveal the layered structure of stratum corneum. This in particular for lipids while water tends to be more evenly distributed. When penetration of the hydrophilic active glycerol and the lipophilic octyl methoxycinnamate, OMC, was studied, a strong correlation between the local distribution of skin constituents and the hydrophilic/lipophilic character of the active was observed.